ANALYSIS OF AN URBAN WATER SUPPLY BY LINEAR PROGRAMMING (Malaysian Journal of Civil Engineering, 2017)
This study investigates the use of linear programming to determine waters distribution schedule from different sources to different water-demanding sectors as well as to determine the scheduled priority use of different types of water resources. For this purpose, the transportation and mixed integer programming algorithms are used. The formulation of both algorithms were analyzed using LINDO program. The method of linear programming (LP) is adopted to optimize water delivery schemes for Icbid City, the second largest city in Jordan. This city as well as the whole country depends mainly upon surface water, and groundwater resources which are scarce and expensive to exploit. The result of the study shows a reasonable argument where all surface water from all sources (Mukhaiba, Wadi Arab and Local supply) is used and none of the groundwater supply is diverted for agricultural purposes due to'its higher cost.